Factors associated with calendar literacy and last menstrual period (LMP) recall: a prospective programmatic implication to maternal health in Bangladesh - Sarker, Bidhan Krishna (BMJ Open, 2020)
OBJECTIVE: To explore the prevalence and determinants of calendar literacy and last menstrual period (LMP) recall among women in Bangladesh. DESIGN: Cross-sectional survey. SETTINGS: Two rural subdistricts and one urban area from three Northern districts of Bangladesh. PARTICIPANTS: We interviewed 2731 women who had a live birth in the last 1 year. PRIMARY AND SECONDARY OUTCOME MEASURES: The primary outcome variable was LMP recall and the secondary outcome was calendar literacy. RESULTS: The majority of participants (65%) correctly mentioned the current date according to the English calendar while 12% mentioned according to the Bengali calendar. During the interview sessions, we used three different calendars: Bengali, English and Hijri to assess calendar literacy. We asked women to mark the current date using the calendar on the day of the interview. Almost 61% women marked the English calendar, 16% marked the Bengali calendar and 4% marked the Hijri calendar correctly. Sixty-three per cent women were found as calendar literate who marked any of the calendars. Among the participants, 58% had calendars available at their home and only 10% of women used calendars to track their LMPs. Overall, 53% women were able to recall their recent LMP. Among the calendar literate, 60% could recall their LMPs. Factors found associated with recalling LMP were: completed eight or more years of schooling (adj.OR 1.39), primigravida (adj.OR 1.88), the richest wealth quintile (adj.OR 1.55) and calendar literacy (adj.OR 1.59). CONCLUSIONS: Despite having reasonable calendar literacy and availability, the use of calendars for tracking LMP found very low. Calendar literacy and sociodemographic characteristics were found as the key factors associated with LMP recall. Maternal, neonatal and child health programmes in low-resource settings can promote a simple tool like calendar and target the communities where ultrasound is not available to ensure accurate LMP recall for early pregnancy registration and timely antenatal care coverage.